Astromesitius, a new genus of Mesitiinae (Hymenoptera, Bethylidae) from the Old World - Barbosa, Diego N.; Azevedo, Celso O. (European Journal of Taxonomy, 2019)
Literature about Mesitiinae Kieffer, 1914 has not been treated extensively from a taxonomic viewpoint in comparison with other subfamilies in Bethylidae Latreille, 1802. Our research on species of Metrionotus Móczár, 1970, Clytrovorus Nagy, 1972 and Sulcomesitius Móczár, 1970 revealed a new hypopygium shape pattern, namely a ‘star-shaped’ hypopygium, which is characteristic of a new genus, Astromesitius gen. nov., with two new species Astromesitius thionyi gen. et sp. nov. and Astromesitius olavoi gen. et sp. nov. The descriptions of both new species are based on male specimens collected in Thailand and the United Arab Emirates. Astromesitius quatei (Móczár, 1977) gen. et comb. nov. is designated as type species for the new genus, which is erected for a total of seven species. The main diagnostic characteristics are the head longer than wide; a clypeus with a median lobe quadrate; an antenna with distinct long setae, with pedicel caliciform, and with flagellomeres long and caliciform; pronotum and anteromesoscutum with longitudinal sulcus indistinct or absent; metapectal-propodeal complex with posterior projection hardly distinct or absent; hypopygium star-shaped; genitalia with aedeagus slender and fusiform.